A ANALISIS KELAYAKAN PADA PEMBIAYAAN MURABAHAH DI BMT MASLAHAH KANTOR CABANG WAGIR - Adhom, Ahmad Syaiqullah; Kusuma, Guntur; Azam, Ilyas Nurul (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2023)
Based on findings in the field, the Account Officer Analysis of BMT Maslahah Wagir Branch has not used the 5C principle (character, capacity, capital, collateral, condition) in analyzing the feasibility of murabahah financing, but only uses two principles, namely character and customer ability, so that if these two principles have been fulfilled then the other three principles will follow these two principles. However, in implementing installments, there are customers who are fluent in payments and there are customers who are late in the payment process. The purpose of the study was to determine the feasibility process of murabahah financing at BMT Maslahah, Wagir Branch. The method used is a qualitative method with a descriptive approach. This research was conducted at BMT Maslahah Wagir Branch. The results show that the feasibility analysis of the financing proposed by the customer will be analyzed by the BMT Maslahah Wagir Branch using the 5C principle (Character, Capacity, Collateral, Capital, Condition). In addition, the strategy in analyzing financing applies various things, such as taking a personal approach to prospective customers in a communicative manner and conducting interviews by preparing various required documents.